Cancer cell targeting by CAR-T cells: A matter of stemness - D’Accardo, Caterina; Porcelli, Gaetana; Mangiapane, Laura Rosa; Modica, Chiara; Pantina, Vincenzo Davide; Roozafzay, Narges; Di Franco, Simone; Gaggianesi, Miriam; Veschi, Veronica; Lo Iacono, Melania; Todaro, Matilde; Turdo, Alice; et al. (Frontiers in Molecular Medicine, 2022)
Chimeric antigen receptor (CAR)-T cell therapy represents one of the most innovative immunotherapy approaches. The encouraging results achieved by CAR-T cell therapy in hematological disorders paved the way for the employment of CAR engineered T cells in different types of solid tumors. This adoptive cell therapy represents a selective and efficacious approach to eradicate tumors through the recognition of tumor-associated antigens (TAAs). Binding of engineered CAR-T cells to TAAs provokes the release of several cytokines, granzyme, and perforin that ultimately lead to cancer cells elimination and patient’s immune system boosting. Within the tumor mass a subpopulation of cancer cells, known as cancer stem cells (CSCs), plays a crucial role in drug resistance, tumor progression, and metastasis. CAR-T cell therapy has indeed been exploited to target CSCs specific antigens as an effective strategy for tumor heterogeneity disruption. Nevertheless, a barrier to the efficacy of CAR-T cell-based therapy is represented by the poor persistence of CAR-T cells into the hostile milieu of the CSCs niche, the development of resistance to single targeting antigen, changes in tumor and T cell metabolism, and the onset of severe adverse effects. CSCs resistance is corroborated by the presence of an immunosuppressive tumor microenvironment (TME), which includes stromal cells, cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs), and immune cells. The relationship between TME components and CSCs dampens the efficacy of CAR-T cell therapy. To overcome this challenge, the double strategy based on the use of CAR-T cell therapy in combination with chemotherapy could be crucial to evade immunosuppressive TME. Here, we summarize challenges and limitations of CAR-T cell therapy targeting CSCs, with particular emphasis on the role of TME and T cell metabolic demands.